H. pylori-associated pathologic findings among Alaska native patients. Issue 1 (1st January 2018) - Nolen, Leisha Diane; Bruden, Dana; Miernyk, Karen; McMahon, Brian J.; Sacco, Frank; Varner, Wayne; Mezzetti, Tom; Hurlburt, Debby; Tiesinga, James; Bruce, Michael G.
ABSTRACT: Helicobacter pylori infection is common among Alaska native (AN) people, however scant gastric histopathologic data is available for this population. This study aimed to characterise gastric histopathology and H. pylori infection among AN people. We enrolled AN adults undergoing upper endoscopy. Gastric biopsy samples were evaluated for pathologic changes, the presence of H. pylori, and the presence of cag pathogenicity island-positive bacteria. Of 432 persons; two persons were diagnosed with gastric adenocarcinoma, two with MALT lymphoma, 40 (10%) with ulcers, and 51 (12%) with intestinal metaplasia. Fifty-five per cent of H. pylori -positive persons had cag pathogenicity island positive bacteria. The gastric antrum had the highest prevalence of acute and chronic moderate–severe gastritis. H. pylori -positive persons were 16 and four times more likely to have moderate–severe acute gastritis and chronic gastritis ( p  < 0.01), respectively. An intact cag pathogenicity island positive was correlated with moderate–severe acute antral gastritis (53% vs. 31%, p  = 0.0003). H. pylori -positive persons were more likely to have moderate–severe acute and chronic gastritis compared to H. pylori -negative persons. Gastritis and intestinal metaplasia were most frequently found in the gastric antrum. Intact cag pathogenicity island positive was correlated with acute antral gastritis and intestinal metaplasia.